PAME Main Achievements; Summary Report 2015-2017 - Protection of the Arctic Marine Environment (PAME) (Protection of the Arctic Marine Environment, 2017)
PAME focuses on the marine agenda of the Arctic Council and provides a unique forum for collaboration on a wide range of activities directed towards the protection and sustainable use of the Arctic marine environment. The programme for the Protection of the Arctic Marine Environment (PAME) was established by the Arctic Council Ministers in Nuuk, Greenland, September 1993.